Land suitability evaluation for duku (Lansium domesticum Corr.) cv. Sumber in Kudus Regency, Central Java, Indonesia - Murrinie, Endang Dewi; Anwar, Khairul; Fairuzia, Fazat; Arini, Nindya; Krestiani, Veronica; Yuliani, Farida; Imanuddin, Muhamad (Journal of Degraded and Mining Lands Management, 2024)
Duku (Lansium domesticum) is an endemic plant in Indonesia with various benefits and distinctive tastes that many people favor. Duku originating from Kudus is known as Duku Sumber, one of the five superior duku varieties. The problem encountered today is the decreasing number of Duku Sumber plants due to land use change, and there has been no effort to increase the plant population. Information on land suitability as a basis for developing crops does not yet exist, so data about land suitability will be used as information on the wider distribution of planting areas in Kudus. This study aimed to evaluate the suitability and land use of Duku Sumber plants in the Kudus Regency. Geographic information systems and matching methods were applied to map the distribution of land suitability for Duku Sumber. The results showed that the potential and actual land suitability class for Duku Sumber are very suitable (S1) and quite suitable (S2) for the Jekulo, Hadipolo, Tenggeles, Golantepus, and Megawon areas, while the slightly suitable (S3) are Klaling, Ngembalrejo, Mejobo and Jati Wetan. The availability of nutrients (na) for nitrogen and potassium is the dominant limiting factor in this area. Nitrogen content in Jati Wetan (0.12%), Klaling (0.19%), and Hadiwarno (0.19%), while potassium content in Ngembalrejo (16.47 ppm) and Mejobo (18.57 ppm). Limitations in this area can be overcome by adding nitrogen and potassium fertilizers to become suitable land.